Innovative transformation of the automotive industry in the context of the global “green” transition - Zvarych, Roman; Farion, Demian (Herald of Economics, 2025)
Introduction. The study explores the innovative transformation of the automotive industry in the context of the global “green” transition, which encompasses transport decarbonization, the mass using of electric vehicles, and the digitalization of production. These processes are driven by intensifying climate challenges, the urgent need to reduce greenhouse gas emissions, and the rapid advancement of innovative technologies in the transport sector. Under current conditions, the green transition in transport is not only an environmental imperative but also a factor of global competition among manufacturers.The purpose of the study. The purpose of the article is to analyze the processes of innovative transformation of the automotive industry in the context of the global “green” transition, with a focus on identifying key technological trends, challenges, and future prospects, as well as on the developing practical recommendations for governments and companies to adapt to the new realities of sustainable development, transport decarbonization, and digitalization.Methods. The research methodology is based on comparative analysis, statistical generalization, and systematization of current scientific sources and analytical reports.Results. The article examines structural changes in the global automotive market, the development of battery technologies, the implementation of digital services (OTA, V2X), prospects for autonomous transport, and shifts in infrastructure development strategies. The findings indicate that China, the United States, and EU countries are the primary drivers of this transformation, accounting for over 90% of global electric vehicle sales. However, regional disparities persist, particularly in access to charging infrastructure, localization of production, and technological sovereignty. Special attention is given to the challenges related to shortages of strategic raw materials (lithium, cobalt, graphite), geo-economic concentration of production, and the need to develop battery recycling.It is concluded that the future of the automotive industry depends on the synergy between government policies, investment in R&D, and international cooperation.Prospects for further research. Future research should focus on analyzing models of government regulation of transport innovation, assessing the effectiveness of tax incentives and institutional support for local production, and ensuring environmental safety in the automotive sector.